Transgenic Mouse Models of Alzheimer’s Disease: An Integrative Analysis - Sánchez-Varo, Raquel María; Mejías-Ortega, Marina; Fernández-Valenzuela, Juan José; Núñez-Díaz, Cristina; Cáceres Palomo, Laura; Vegas-Gómez, Laura; Sánchez-Mejías, Elisabeth; Trujillo-Estrada, Laura Isabel; Moreno-González, Inés; García-León, Juan Antonio; Vizuete, María Luisa; Vitorica Ferrández, Javier; et al. (MPDI, 2022)
Alzheimer’s disease (AD) constitutes the most prominent form of dementia among elderly individuals worldwide. Disease modeling using murine transgenic mice was first initiated thanks to the discovery of heritable mutations in amyloid precursor protein (APP) and presenilins (PS) genes. However, due to the repeated failure of translational applications from animal models to human patients, along with the recent advances in genetic susceptibility and our current understanding on disease biology, these models have evolved over time in an attempt to better reproduce the complexity of this devastating disease and improve their applicability. In this review, we provide a comprehensive overview about the major pathological elements of human AD (plaques, tauopathy, synaptic damage, neuronal death, neuroinflammation and glial dysfunction), discussing the knowledge that available mouse models have provided about the mechanisms underlying human disease. Moreover, we highlight the pros and cons of current models, and the revolution offered by the concomitant use of transgenic mice and omics technologies that may lead to a more rapid improvement of the present modeling batter
Keywords: Alzhéimer, Enfermedad de; Sistema nervioso - Degeneración; Neuroglia; Alzheimer’s disease; Transgenic mice; Amyloid; Tau; Microglia Astrocytes; Oligodendrocytes; Neurodegeneration